RETRACTED: Resources and potential of renewable energy sources: methods for calculating and data sources - Frid Semen; Muminov Shermuhammad (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001